PELAYANAN UJI KIR DI UPTD PENGUJIAN KENDARAAN BERMOTOR PADA DINAS PERHUBUNGAN KOTA PEKANBARU - Jelita Angelika Rajagukguk; Nur Laila Meilani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This vehicle test is determines for chek the worthines of vehicle, cheking is will do on a physical check. Testing conducted is the test of vehicles used as public transportation and logistic transportation. The aim of this study is to determine the service of vehicle testing from the administrastion and physical testing of the vehicle. this research using basic concept of public service standard which taken from joko widodo theory (2001), which explains that there are 5 indicators of public service standards are service procedures, completion time, service products, service costs, facilities and infrastructure, and officer competence. the authors use qualitative research methods by assessing data descriptively. in collecting research data using interview technique, observation, and documentation.the results of this study can be seen that the service KIR Test at Technical. Implementation Unit Area Vehicle Testing in the Department of Transportation is quite good but there are still problems that are found that is the completion time is not in accordance with the established Standard operational procedures, facilities and infrastructure not yet available, there is many testing tools are not working optimally, the set fee has not been transparent including new charges that are not submitted and explained to the public and less of socialization about how important KIR Test at Technical Implementation Unit Area Test Testing vehicle in department of transportation in pekanbaruKeywords: Public Services, KIR, Motor vehicle